Desenvolvimento de um inversor fotovoltaico trifásico não isolado conectado à rede elétrica - Giacomini, Julian Cezar (2015)
This Master Thesis presents the development of a grid-connected transformerless three-phase photovoltaic inverter. The Neutral Point Clamped (NPC) three-level inverter was chosen for implementation. The grid connection is made with a modified LCL filter (MLCL), where the common point of the output filter capacitors is connected directly to the dc bus central point (neutral point). The MLCL filter reduces the leakage current of photovoltaic system and attenuates the current harmonics injected in the grid. A passive damping of MLCL filter resonance peak was employed in order to avoid instability in the grid connection. In this sense, this Master Thesis contributes proposing a passive damping design method which is based not only on the stability requirement, but also considers the leakage current of photovoltaic system, once that passive damping impacts on the high frequency components of voltage on parasitic capacitance. Therefore, based on leakage current limit and current loop stability, a range for the damping resistance was obtained. The control system of the threephase inverter was developed in a synchronous reference frame (dq0), where the proper alignment with the grid voltage reference vector allows the independent control of active and reactive power inject in the grid. Simulation and experimental results are shown to evaluate the inverter performance and to validate the theoretical analysis.